2019
DOI: 10.3390/cells8040368
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Tonsil-Derived Mesenchymal Stem Cells Improves Glucose Tolerance in High Fat Diet-Induced Diabetic Mice via Insulin-Like Growth Factor-Binding Protein 5-Mediated Endoplasmic Reticulum Stress Modulation

Abstract: Type 2 diabetes mellitus (T2DM) is a prevalent chronic metabolic disorder accompanied by high blood glucose, insulin resistance, and relative insulin deficiency. Endoplasmic reticulum (ER) stress induced by high glucose and free fatty acids has been suggested as one of the main causes of β-cell dysfunction and death in T2DM. Stem cell-derived insulin-secreting cells were recently suggested as a novel therapy for diabetes. In the present study, we demonstrate the therapeutic potential of tonsil-derived mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
(99 reference statements)
2
12
0
Order By: Relevance
“…In our study, CHOP and p-JNK were significantly elevated after IRI, indicating that both pathways are activated in the IR porcine liver due to excessive ERS. Consistent with the findings of Lee et al (2019) that tonsilderived MSCs have an inhibitory effect on CHOP, we found that the ADSCs also downregulated this protein in the injured liver. Thus, ADSCs can alleviate hepatic IRI damage by reducing ERS-induced apoptosis as well.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, CHOP and p-JNK were significantly elevated after IRI, indicating that both pathways are activated in the IR porcine liver due to excessive ERS. Consistent with the findings of Lee et al (2019) that tonsilderived MSCs have an inhibitory effect on CHOP, we found that the ADSCs also downregulated this protein in the injured liver. Thus, ADSCs can alleviate hepatic IRI damage by reducing ERS-induced apoptosis as well.…”
Section: Discussionsupporting
confidence: 91%
“…Diabetes is characterized by persistent hyperglycemia, which may lead to diverse representative complications including cardiomyopathy, nephropathy, diabetic foot, and diabetic neuropathy, which significantly contribute to the associated rates of morbidity and mortality [ 2 ]. Additionally, diabetes may accelerate the deterioration of respiratory function with characteristic anatomical and biological changes to the diabetic lung [ 5 , 23 , 24 ]. These abnormalities affect lung volume, pulmonary diffusing capacity, ventilation control, bronchomotor tone, and neuroadrenergic bronchial innervation.…”
Section: Discussionmentioning
confidence: 99%
“…Acute myocardial infarction is associated with higher mortality rates in patients with diabetes [ 3 ]. Diabetes also increases susceptibility myocardial ischemia/reperfusion (I/R) injury, which can induce endoplasmic reticulum stress (ERS) [ 4 , 5 ]. ERS refers to ischemia, hypoxia, oxidative stress, and glucose/nutrition abnormalities where material deficiencies promote abnormal glycosylation reactions and calcium ion homeostasis, significantly increasing the number of unfolded proteins in the ER.…”
Section: Introductionmentioning
confidence: 99%
“…The conditioned media of various MSCs were obtained, as previously reported with a few modifications [18]. Cells at 80% confluence were washed twice with PBS and incubated in serum-free DMEM for 48 h. The conditioned media were collected, filtered by centrifugation at 190 × g at room temperature for 5 min to remove suspended cells and concentrated using an Amicon Ultra Centrifugal Filter unit (molecular weight cut-off value of 3KDa; Merck, Darmstadt, Germany) by high-speed centrifugation at 5000 × g at 4°C for 1 h. Nano-liquid chromatography coupled with tandem mass spectrometry (nano LC-MS/MS) analysis using the Mascot algorithm (Matrix Science, Boston, MA, USA) was performed, as previously reported [13].…”
Section: Proteomicsmentioning
confidence: 99%
“…Our research group has been investigating therapeutic effects of TMSCs and their mechanisms of action. By performing transcriptomic and proteomic analyses, we screened molecules with higher expression levels in TMSCs compared to bone marrow (BM) or adipose tissue (AD) MSCs [12,13]. Furthermore, we have reported immune modulating, anti-fibrotic, and insulin sensitizing effects of TMSCs via secreting PD-L1, IL-1Ra, and IGFBP5, respectively [13][14][15].…”
Section: Introductionmentioning
confidence: 99%